Corporate Social Responsibility in the Rule of Law and Welfare State Concept - Busyra Azheri (Faculty of Law, Hasanuddin University, 2016)
The provision of the Law Number 40 of 2007 concerning Limited Company on Corporate Social Responsibility has changed the nature of such responsibility from voluntary into mandatory. Similarly, it strengthened welfare state (verzorgings staat) concept as commanded by Article 33 (3) and (4) of the 1945 Constitution of the Republic of Indonesia. Denaturing of this Corporate Social Responsibility is progressively assured by the Decision of Indonesian Constitutional Court, so that responsibility must be performed as legal responsibility or mandatory.